Freedom: the second peculiar institution - Rinaldi Semione, Juliana (2021)
This thesis answers the question, “What is freedom from slavery?” Rather than pursuing this question from a philosophical or political position, this research takes the original approach of putting the question directly to key antislavery stakeholder groups: law enforcement professionals, victim service providers, and survivors. The result is the first collection of shared conceptions of freedom from across the antislavery field and the advancement of a composite definition of freedom.